2002
DOI: 10.7547/87507315-92-4-200
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tenodesis for Retrocalcaneal Surgery

Abstract: Retrocalcaneal surgery is complex and difficult. Over the years, many different approaches to retrocalcaneal surgery have been described. Partial or total release of the tendo Achillis is often necessary, with reattachment being of paramount importance to allow for optimal function following surgery. Although numerous anchoring devices have been introduced for tendo Achillis reattachment, the authors have found the DePuy TiMAX Spider Plate (DePuy ACE, Warsaw, Indiana) to be superior. This article describes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Operative care has been described as a lateral, medial, or midline incision through skin and a U-shaped full-thickness Achilles detachment from its insertion centrally, resection of the exostosis and inflamed tendon, and reinsertion of the tendon with 1 or 2 suture anchors. Many different anchor types have been described for the use of tendon to bone healing (5)(6)(7)(8)(9). Reattachment at physiologic tension is quite important to prevent contracture and laxity.…”
mentioning
confidence: 99%
“…Operative care has been described as a lateral, medial, or midline incision through skin and a U-shaped full-thickness Achilles detachment from its insertion centrally, resection of the exostosis and inflamed tendon, and reinsertion of the tendon with 1 or 2 suture anchors. Many different anchor types have been described for the use of tendon to bone healing (5)(6)(7)(8)(9). Reattachment at physiologic tension is quite important to prevent contracture and laxity.…”
mentioning
confidence: 99%
“…Achilles tendon bone anchor reattachment is not a novel concept. [3][4][5] A new suture technique, the Achilles Tendon SutureBridge (Arthrex, Inc, Naples, Florida), offers a strong anchor reattachment of the Achilles tendon to the posterior calcaneus. The studies performed by Arthrex in testing have shown a greatly increased contact pressure and fixation strength compared with a standard single row anchor repair.…”
Section: Achilles Tendon Suturebridge Techniquementioning
confidence: 99%